Pengaruh kinerja keuangan terhadap nilai perusahaan pada perusahaan real estate di Bursa Efek Indonesia - Ni Putu Diah Prabawati; I Wayan Gde Yogiswara Darma Putra; Ni Made Vita Indriyani (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study aims to examine the influence of financial performance on the value of companies in real estate companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Financial performance was measured using profitability proxied by Return on Assets (ROA), Liquidity with Current Ratio (CR), Solvency with Debt to Equity Ratio (DER), and activities with Total Asset Turnover (TATO), while company value was measured using Price to Book Value (PBV). This study uses a quantitative approach with secondary data in the form of annual financial statements and company share prices. The sample was determined through purposive sampling techniques so that 161 company observations from 92 companies were obtained during 3 years of observation. Data analysis was carried out by regression of panel data using E-views. The results of the study showed that solvency had a positive effect on the company's value. Profitability, liquidity, and activity had no effect on the company's value. These findings indicate that during the recovery period of the property sector, the market is more responsive to the company's funding structure than to profitability, short-term liquidity, or asset turnover efficiency.